Fungal metabolite 6-pentyl-α-pyrone reduces canine coronavirus infection - Claudia Cerracchio; Luca Del Sorbo; Francesco Serra; Alessia Staropoli; Maria Grazia Amoroso; Francesco Vinale; Filomena Fiorito (Heliyon, 2024)
Canine coronavirus (CCoV) can produce a self-limited enteric disease in dogs but, because of notable biological plasticity of coronaviruses (CoVs), numerous mutations as well as recombination events happen leading to the emergence of variants often more dangerous for both animals and humans.Indeed, the emergence of new canine-feline recombinant alphacoronaviruses, recently isolated from humans, highlight the cross-species transmission potential of CoVs.Consequently, new effective antiviral agents are required to treat CoV infections. Among the candidates for the development of drugs against CoVs infection, fungal secondary metabolites (SMs) represent an important source to investigate. Herein, antiviral ability of 6-pentyl-α-pyrone (6 PP), a SM obtained by Trichoderma atroviride, was assessed against CCoV. During in vitro infection, nontoxic concentration of 6 PP significantly increased cell viability, reduced morphological signs of cell death, and inhibited viral replication of CCoV. In addition, we found a noticeable lessening in the expression of aryl hydrocarbon receptor (AhR), a strategic modulator of CoVs infection.Overall, due to the variety of their chemical and biological properties, fungal SMs can decrease the replication of CoVs, thus identifying a suitable in vitro model to screen for potential drugs against CoVs, using a reference strain of CCoV (S/378), non-pathogenic for humans.